Augmentation of economic status of Bastar tribals through integrated (crop, livestock, poultry, duck, fish) farming system - Tiwari, S P; Saxena, Ravi R; Nandeha, K L; Vardia, H K; Sharma, R B; Rajagopal, S (The Indian Journal of Animal Sciences, 2012)
Investigations were carried out to find out a sustainable mixed farming model which is economically viable integrating the crop livestock poultry, duck and fish farming on 1.5 ha land holding. Different viable combinations, viz. (i) arable, (ii) mixed farming with 2 crossbred cows (Jersey X Red Sindhi), (iii) mixed farming with 2 buffaloes (Murrah), (iv) mixed farming with 2 crossbred cows + fish, (common carp + grass carp + rohu + catla mixed), (v) mixed farming with 2 buffaloes, (vi) mixed farming with 2 crossbred cows + 15 goats (Jammunapari) + 10 poultry + 10 ducks + fish were developed to find out the best package on this land holding of 1.5 ha suitable for the tribal region. A model having 2 crossbred cows + 15 goats + 10 poultry birds + 10 ducks on 0.25 ha area including for own living + fish (0.15 ha pond) alongwith crop cultivation (on 1.1 ha) was the best with a net income of Rs 44 911/year against arable farming alone (Rs 24 093) with a cost returns of 1 : 2 and employment generation of 380-man-day.